2017
DOI: 10.1111/jdi.12610
|View full text |Cite
|
Sign up to set email alerts
|

Impact of postprandial hyperglycemia at clinic visits on the incidence of cardiovascular events and all‐cause mortality in patients with type 2 diabetes

Abstract: Aims/IntroductionWe evaluated the impact of postprandial hyperglycemia at clinic visits on the incidence of cardiovascular diseases (CVD) and all‐cause mortality independently of mean glycosylated hemoglobin in type 2 diabetes patients in a real‐world setting.Materials and MethodsThe present retrospective observational cohort study included 646 type 2 diabetes patients. All of the participants had their initial consultations at the Institute for Diabetes Care and Research, Asahi Life Foundation affiliated Maru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 35 publications
0
18
0
Order By: Relevance
“…This finding is significant because a previous study suggests that postprandial hyperglycemia confers an increased risk of cardiovascular disease and death [28] and a low incidence of this practice is worrisome. As already mentioned in the American Diabetic Association guidelines [14], we also observed that people with a low frequency of SMBG failed to adjust their treatment regimens.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding is significant because a previous study suggests that postprandial hyperglycemia confers an increased risk of cardiovascular disease and death [28] and a low incidence of this practice is worrisome. As already mentioned in the American Diabetic Association guidelines [14], we also observed that people with a low frequency of SMBG failed to adjust their treatment regimens.…”
Section: Discussionmentioning
confidence: 99%
“…In accordance with Parkin C, et al [ 27 ], we found that a majority of the participants who used glucometers monitored their fasting blood glucose alone while failing to monitor postprandial glucose. This finding is significant because a previous study suggests that postprandial hyperglycemia confers an increased risk of cardiovascular disease and death [ 28 ] and a low incidence of this practice is worrisome. As already mentioned in the American Diabetic Association guidelines [ 14 ], we also observed that people with a low frequency of SMBG failed to adjust their treatment regimens.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of type 2 diabetes (T2D) is increasing globally [ 1 ]. In patients with T2D, postprandial hyperglycemia has shown to raise the incidence of cardiovascular disease (CVD) and all-cause mortality [ 2 , 3 ]. Postprandial hyperglycemia is often accompanied by postprandial hypertriglyceridemia, which acts as a further risk factor for CVD.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical examinations and laboratory methods used in the present study have been described previously. To summarize, blood samples were collected regardless of fasting or postprandial status.…”
Section: Methodsmentioning
confidence: 99%